Match outcome and running performance among Champions League soccer players - Modric, T.; Gabrilo, G.; Peric, M. (Studia Sportiva, 2022)
This study aimed to examine position-specific differences in running performance (RP) according to the match outcome in UEFA Champions League (UCL). The players` RPs (n=244) were collected during UCL group stage matches (n=20) in the 2020/21 season using semiautomatic optical system InStat Fitness, and classified according to their playing positions as: central defenders (CD; n=79), fullbacks (FB; n=65), central midfielders (CM; n=55), wide midfielders (WM; n=28) and forward (FW; n=17). The RP variables included: total distance covered, low-intensity (LIR) (<14.3km/h), running (14.4-19.7 km/h), high-speed running (HSR) (19.8-25.1 km/h), and sprinting (>25.2 km/h). Match outcome was observed as win, draw and loss. One-way analysis of variance (ANOVA) was used to examine differences in RP according to the match outcome. Significant differences in TD (F-test=4.16, p=0.02) and LIR (F-test=4.51, p=0.01) among match outcomes were observed for FBs. Specifically, FBs covered significantly greater TD when their team won than when lost (p=0.03, d=0.79). In addition, FBs` LIR was significantly greater in won matches than in drew (p=0.04, d=0.92) and lost matches (p=0.03, d=0.77). The RP of players on all other playing position were similar irrespective to the match outcome (F-test=0.08 to 2.84, all p>0.05). These results indicated that winning UCL matches is not strongly influenced by players` physical performance, except for FBs who tended to covered greater total- and low- distance when their teams won. This study indicated limited overall influence of RP on success in matches at elite-level soccer. The findings from this study may help soccer coaches to ensure optimal physical preparation of players in elite soccer.